13+2(1-u)=8u-5(u+7)

Simple and best practice solution for 13+2(1-u)=8u-5(u+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+2(1-u)=8u-5(u+7) equation:


Simplifying
13 + 2(1 + -1u) = 8u + -5(u + 7)
13 + (1 * 2 + -1u * 2) = 8u + -5(u + 7)
13 + (2 + -2u) = 8u + -5(u + 7)

Combine like terms: 13 + 2 = 15
15 + -2u = 8u + -5(u + 7)

Reorder the terms:
15 + -2u = 8u + -5(7 + u)
15 + -2u = 8u + (7 * -5 + u * -5)
15 + -2u = 8u + (-35 + -5u)

Reorder the terms:
15 + -2u = -35 + 8u + -5u

Combine like terms: 8u + -5u = 3u
15 + -2u = -35 + 3u

Solving
15 + -2u = -35 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
15 + -2u + -3u = -35 + 3u + -3u

Combine like terms: -2u + -3u = -5u
15 + -5u = -35 + 3u + -3u

Combine like terms: 3u + -3u = 0
15 + -5u = -35 + 0
15 + -5u = -35

Add '-15' to each side of the equation.
15 + -15 + -5u = -35 + -15

Combine like terms: 15 + -15 = 0
0 + -5u = -35 + -15
-5u = -35 + -15

Combine like terms: -35 + -15 = -50
-5u = -50

Divide each side by '-5'.
u = 10

Simplifying
u = 10

See similar equations:

| 14X=6X+16 | | 12x+48=5x-117 | | (6x-7y)(6x-7y)= | | 5x+8=-8 | | 5+(3y+3)=-(3-4)+8 | | 7m+8=3m-16 | | 6x^2=27x+15 | | 4(a+2)=2(-2+a)-4 | | 2p+18=p-8 | | 27-5X=-3 | | 7+5p+6P=7p-1+5p+16 | | 3(x+9y)=3(x+9y) | | -4(6x-1)-3(5x-6)=12x+5 | | 10n-22=8n-14 | | 30x^3+25x^2+5x=0 | | 5x+9y=164x-6y=26 | | 4x+3(6x-5)= | | 0.33333y=-7 | | (8a+9)(8a-9)= | | f(2)=7-3(2)(2) | | 9x+15=-2x-18 | | f(3)=7-3(2)(2) | | 9n+14=11n | | 4x-1=2x-7isx | | 11(3w-2)-14w=2w+3 | | 5x+9y=16 | | -8-8(-z+6)=7(-6z-6)-8 | | 20x-16=-17 | | -2x+-6=-2x+-2-4 | | 6-2(2w-1)=9w-2(9+w) | | 24=-6+3y | | 9q=-36 |

Equations solver categories